Studi Fenomenologi: Pengalaman Klien Lansia dalam Melakukan Perawatan Diabetes Mellitus Tipe 2 - Nadirawati Nadirawati; Irfan Pratama (Journal of Telenursing (JOTING), 2021)
This study aims to gain an in-depth understanding of the meaning of type 2 Diabetes Mellitus (DM) treatment for elderly clients in Puskesmas Cimahi Selatan's work area and how they interpret this experience. This study used a qualitative approach with a descriptive phenomenological design with in-depth interviews. Participants in this study were elderly clients with type 2 diabetes. The data collected were in the form of recorded interviews and field notes which were analyzed using the Collaizi technique. The results of this study identified six themes, including; 1) physical response experienced by DM sufferers; 2) psychological response experienced by DM sufferers; 3) adherence to medication; 4) adherence to diet; 5) efforts to achieve healing; 6) expectations of people with DM. In conclusion, of the six informants who experienced diabetes they experienced several physical and psychological problems. Some were not obedient to the diet, and the way the parents dealt with the situation was by using pharmacological and non-pharmacological drugs. Besides, even though they have had diabetes for a long time, almost all participants hoped to recover from their illness. Keywords: Type 2 Diabetes Mellitus, Qualitative, Caring